Digital Transition, Sustainability and Readjustment on EU Tourism Industry: Economic & Legal Analysis (Law, State and Telecommunications Review, 2023)
[Purpose] To explain why the tourism sector is so relevant for European economies (specially in Spain), but there are many failures and paradoxes in its public management during the digital transition (from Welfare State Economy to Wellbeing Economics), with more troubles because the COVID-19 crisis and the Ukraine war.[Methodology/Approach/Design] This is a heterodox review on Political Economy, Macroeconomics, Labor Economics and Business Management, focused on the readjustment effect into the tourism industry due to the impact of the digital transition and its aggravation with the COVID-19 crisis and the Ukraine war. The objective of this review is to try to explain the current situation (not to predict anything), so it is applied the theoretical and methodological frameworks of the heterodox synthesis, mixing the genetic-causal approach by Austrian Economics with the historical-comparative approach by New-Institutional Economics.[Findings] This review explains the failures and paradoxes in the public management of the tourism sector transition because there is a resistance to change, and there is not an adaptation in the production process and its economic structure. In an overview, the resistance is observed in the switch of economic model (from Welfare State Economy to Wellbeing Economics) and labor relations (from repetitive-technicians directed to talent collaborators with autonomy). Focused in the tourism industry, the digital transition can help to offer better travel experiences.[Practical Implications] The readjustment effect can help to improve the European economies, specially for the Spanish case, where the tourism industry is the main sector of its economy. With this proposal is possible to take the digital advantage and its changes to become more productive and profitable, with greater wellbeing level for workers and society.[Originality] This review introduces the heterodox synthesis, moving from econometric foundations (based on statistical approach to get predictions and equilibrium point), to mainline foundations (based on principles and empirical evidence on incentives, efficiency and institutional-quality).